Carryover effects in amphibians: Are characteristics of the larval habitat needed to predict juvenile survival?. Issue 6 (1st September 2013) - Earl, Julia E.; Semlitsch, Raymond D.
Abstract : Carryover effects occur when experiences early in life affect an individual's performance at a later stage. Many studies have shown carryover effects to be important for future performance. However, it is currently unclear whether variation in later environments could overwhelm factors from an earlier life stage. We were interested in whether similar patterns would emerge under the same experimental design with similar taxa. To examine this, we implemented a four‐way factorial experimental design with different forestry practices on three species of anurans (each examined in different years) in the aquatic larval environment and terrestrial juvenile environment in outdoor mesocosms in central Missouri, USA. Using Cormack‐Jolly‐Seber mark–recapture models implemented in program MARK, we investigated whether one environment or both environments best predicted terrestrial juvenile survival. We found only limited evidence of carryover effects for one of three species in one time period. These were the effects of time to metamorphosis and body condition at metamorphosis predicting leopard frog ( Lithobates sphenocephalus ) survival. However, both effects were counterintuitive and/or very weak. For wood frogs ( L. sylvaticus ), all of the variables predicting survival had confidence intervals that included zero, but very low survival may have limited our ability to estimate parameters. The terrestrial environment was important for predicting survival in both American toads ( Anaxyrus americanus ) and southern leopard frogs. The partial harvest forest tended to increase survival relative to control forest and early‐successional forest in American toads. Alternately, early‐successional forest with downed wood removed increased survival for leopard frogs, but this treatment was no different from control forest for American toads. Previous studies have shown negative effects of recent clearcuts on terrestrial amphibians. It appears that vegetative regrowth after just a few years can mitigate these initial negative effects. Our study shows that variation in later environments probably can overwhelm variation from earlier environments. However, previous evidence of carryover effects suggests that more research is needed to predict when carryover effects are likely to occur.